Integrating Innovations and Traditions in Teacher Education Through Project-Based Learning - Tasbulatovа Gulnara; Radzitskaya , Yadviga; Baigozhina, Zhanar; Aubakirova , Aliya (Pedagogy and Psychology, 2025)
The study examines project-based learning as a tool for integrating innovations and traditions in teacher training, addressing the need for more effective approaches to preparing future educators who can balance innovative methodologies with traditional pedagogical values and cultural heritage preservation. Methodology and Methods. The research employed literary analysis and empirical methods including survey and pedagogical experiment to determine the possibility of using an active model of project-based learning in teacher preparation, using elementary education as an example. A comparative analysis was conducted between experimental and control groups to evaluate the effectiveness of the proposed approach. Results. The study revealed that the current level of development of project-based learning in pedagogical universities is low, indicating a need for its enhancement. Seven integration-focused projects were tested in practice: cultural heritage in the classroom, innovative technologies in teaching, environmental education through traditions, grandparents’ stories, creative workshop, from traditions to innovations, and virtual tours of historical places. The effectiveness of the model was confirmed through comparative analysis, which demonstrated positive impact on students’ knowledge and skills levels in the experimental group. Scientific novelty. The research establishes a theoretical framework for integrating innovations and traditions through project-based learning in teacher education, providing a systematic approach to teaching future educators how to incorporate innovative approaches into traditional teaching while maintaining respect for cultural heritage. Practical significance. The developed model and tested projects provide practical tools for pedagogical universities to enhance teacher preparation programs, enabling future teachers to effectively integrate innovative methodologies with traditional values in their professional practice and improve the quality of elementary education.